Pengembangan Sistem Manajemen Kuis Berbasis Web menggunakan Metode Rapid Application Development - Hikmal Adi Wibowo; Siska Narulita (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
Digital-based evaluation is increasingly utilized across various fields of education and training. This study focuses on the development and analysis of a web-based quiz management system that facilitates interaction between users and administrators. The research involves implementing a user dashboard for quiz participation and an admin dashboard for managing questions and quiz results. The methodology includes a case study on system testing, user needs analysis, and evaluation of system effectiveness using both quantitative and qualitative approaches. The findings indicate that the system enhances evaluation efficiency and simplifies quiz data management. The study concludes that web-based systems play a crucial role in supporting evaluation and learning management.